2021
DOI: 10.1111/gcb.15721
|View full text |Cite
|
Sign up to set email alerts
|

Boreal forest soil carbon fluxes one year after a wildfire: Effects of burn severity and management

Abstract: The extreme 2018 hot drought that affected central and northern Europe led to the worst wildfire season in Sweden in over a century. The Ljusdal fire complex, the largest area burnt that year (8995 ha), offered a rare opportunity to quantify the combined impacts of wildfire and post‐fire management on Scandinavian boreal forests. We present chamber measurements of soil CO2 and CH4 fluxes, soil microclimate and nutrient content from five Pinus sylvestris sites for the first growing season after the fire. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 76 publications
2
8
0
1
Order By: Relevance
“…However, they were comparable to averaged losses from experimental Scots pine stands in Siberia (0.992 kg C m −2 ) (Ivanova et al, 2011), though half that of surface wildfire in Siberian pine (Pinus sibirica) stands (1.69 kg C m −2 ) (Kukavskaya et al, 2017). Interestingly, this study found average C stock reduction to be nearly equivalent to that estimated in a Scots pine crown fire, selected for its high severity, within the largest, most extreme wildfire occurring in Sweden during 2018 (0.80 kg C m −2 ) (Kelly et al, 2021). In contrast, the largest wildfire occurring in Sweden during 2014 released an estimated 4.50 kg C m −2 from Scots-pine-dominated stands, which lies just above the 93rd percentile of C loss estimates within the 50-plot network of the current study (Granath et al, 2021).…”
Section: Moisture and Summer 2018 Anomaliesmentioning
confidence: 51%
“…However, they were comparable to averaged losses from experimental Scots pine stands in Siberia (0.992 kg C m −2 ) (Ivanova et al, 2011), though half that of surface wildfire in Siberian pine (Pinus sibirica) stands (1.69 kg C m −2 ) (Kukavskaya et al, 2017). Interestingly, this study found average C stock reduction to be nearly equivalent to that estimated in a Scots pine crown fire, selected for its high severity, within the largest, most extreme wildfire occurring in Sweden during 2018 (0.80 kg C m −2 ) (Kelly et al, 2021). In contrast, the largest wildfire occurring in Sweden during 2014 released an estimated 4.50 kg C m −2 from Scots-pine-dominated stands, which lies just above the 93rd percentile of C loss estimates within the 50-plot network of the current study (Granath et al, 2021).…”
Section: Moisture and Summer 2018 Anomaliesmentioning
confidence: 51%
“…We found the declines in R h increased with the increasing severity gradient, which could be attributed to the direct combustion of vegetation, associated mycorrhizal fungi and free‐living microbial biomass together with the increased nutrient volatilization (Dooley & Treseder, 2012; McLauchlan et al, 2020). Some microbial taxa are particularly vulnerable to high‐severity fire because tree mortality prevents labile C input to decomposers and the rhizosphere and its symbiont (Day et al, 2019; Kelly et al, 2021). Given the lack of litter protection after the high‐severity fire, large amounts of ashes may be lost with runoff, which impedes the substrate acquisition of microorganisms and thereby could cause a decline in R h (Hu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fire immediately reduces R a due to root mortality or injury; while fire can stimulate R h by raising soil temperature and increasing labile inputs in the short time. However, the impacts on R h might be offset by the combustion of microbial biomass during high-severity fires (Kelly et al, 2021). The long-term responses of R h were highly variable depending on factors such as plant recovery and succession.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rise in nutrient concentration in soils following vegetation destruction may additionally be affected by dead roots and other organic material and the absent or reduced plant uptake of nutrients (Kulmala et al, 2014; Rasmussen et al, 2020). Vegetation recovery (and corresponding changes in the soil) after a tundra fire seems to depend on the fire severity (Kelly et al, 2021) as well as the availability and uptake of inorganic N (Jiang et al, 2015). A comprehensive study suggests fire severity at higher latitudes is primarily driven by belowground fuel availability in form of biomass and secondarily by aboveground biomass (Walker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%